The Adam Mickiewicz University Nature Collections IT system (AMUNATCOLL): metadata structure, database and operational procedures - Lawenda, Marcin; Wiland-Szymańska, Justyna; Nowak, Maciej M.; Jędrasiak, Damian; Jackowiak, Bogdan (Biodiversity: Research and Conservation, 2022)
This paper describes the procedures and operational aspects related to the proper storage and handling of taxonomic, biogeographic and ecological data of biological specimens digitised under the AMUNATCOLL project. In the introductory phase of this process, the definition of the metadata is carried out, which is the formal handler of the structure, based upon the analysis of existing standards. The set of parameters derived from the standard is extended by data that is important according to the point of view of the specificity and functionality of the developed system. Subsequently, the database, as a key element in many IT systems, must be set up for data storage along with the suitable structure that reinforces efficiency. The process of preparing and casting a large amount of data requires automated procedures with dedicated tools attached. These approaches address a variety of processes starting from data preparation, where occasionally conversion must occur, aggregation and finally validation, which guarantees that data apply defined rules. Above all, dedicated operational procedures must be defined and applied to enable proper handling of the entire process.